Molecular Investigation of Recurrent Streptococcus iniae Epizootics Affecting Coral Reef Fish on an Oceanic Island Suggests at Least Two Distinct Emergence Events - Solène Irion (Frontiers Media S.A., 2021)
Streptococcus iniae is an emerging zoonotic pathogen of increasing concern for aquaculture and has caused several epizootics in reef fishes from the Caribbean, the Red Sea and the Indian Ocean. To study the population structure, introduction pathways and evolution of S. iniae over recurring epizootics on Reunion Island, we developed and validated a Multi Locus Sequence Typing (MLST) panel using genomic data obtained from 89 isolates sampled during epizootics occurring over the past 40years in Australia, Asia, the United States, Israel and Reunion Island. We selected eight housekeeping loci, which resulted in the greatest variation across the main S. iniae phylogenetic clades highlighted by the whole genomic dataset. We then applied the developed MLST to investigate the origin of S. iniae responsible for four epizootics on Reunion Island, first in inland aquaculture and then on the reefs from 1996 to 2014. Results suggest at least two independent S. iniae emergence events occurred on the island. Molecular data support that the first epizootic resulted from an introduction, with inland freshwater aquaculture facilities acting as a stepping-stone. Such an event may have been facilitated by the ecological flexibility of S. iniae, able to survive in both fresh and marine waters and the ability of the pathogen to infect multiple host species. By contrast, the second epizootic was associated with a distinct ST of cosmopolitan distribution that may have emerged as a result of environment disturbance. This novel tool will be effective at investigating recurrent epizootics occurring within a given environment or country that is despite the fact that S. iniae appears to have low genetic diversity within its lineage.